Content selection strategies in vlogging: Analysing esl students’ decision- making at Universiti Malaysia Sabah - Nurul Nazira Hamzah; Esther Jawing (The Malaysian English Language Teaching Association, 2025)
This study investigates the content selection process for vlogging projects among ESL students in an English classroom. Employing a mixed-methods approach, data were collected from 51 students using an open-ended questionnaire. Thematic analysis was used to interpret qualitative responses, while descriptive statistics, cross-tabulation, and chi-square tests were conducted to examine relationships between variables. The findings reveal that students consider multiple factors when selecting vlog content, with entertainment value (20.0%), creativity (18.2%), viewers’ benefits (16.4%), and personal experiences (16.4%) identified as the most influential. Other factors include educational value (10.9%), content quality (9.1%), and personal preferences (9.0%). Students produced vlogs across a range of themes, including traditional culture, food reviews, personal challenges, health-related activities, and product reviews. Social media exposure, particularly through platforms such as YouTube and Instagram, significantly influenced their content decisions. These findings offer valuable insights into the decision-making process underlying students' vlogging projects, emphasizing the importance of creativity, audience engagement, and digital media influence. The study contributes to the pedagogical understanding of vlogging as a tool in English language instruction and offers practical implications for educators seeking to integrate vlogging into the ESL classroom.